The Effect of IFRS Adoption on Corporate Social Responsibility Disclosure: The Moderating Role of Multinational Activities - Kwakye, Teddy Ossei; Coffie, William; Kpeli, Parrendah Adwoa; Abor, Patience Aseweh (Journal of Leadership, Accountability and Ethics, 2022)
This study examines the effects of IFRS adoption and Degree of Multinational Activities (DMA) on Corporate Social Responsibility Disclosure (CSRD) and whether DMA increases the IFRS adoption effect on CSRD. We used content analysis based on an adapted CSRD index score created by Hackston and Milne (1996) to examine the annual reports of 28 publicly traded corporations from 2003 to 2013. We estimate the quantity and quality of CSRD as a function of IFRS adoption and multinational activity, as well as the interactive effect of DMA and IFRS adoption, based on the purpose and hypotheses of our study. The key findings reveal that the implementation of the International Financial Reporting Standards (IFRS) positively affects the quantity and quality of corporate social responsibility disclosure. Interestingly, the degree of multinational activities (DMA) also increases the IFRS adoption effect on both quality and quantity of CSRD. For practitioners, this study reveals that IFRS adoption is associated with several effects on the CSR disclosures.